2006
DOI: 10.1080/14015430500456739
|View full text |Cite
|
Sign up to set email alerts
|

The role of F3 in the vocal expression of emotions

Abstract: The present study investigates the role of F3 in the perception of valence of emotional expressions by using a vowel [a:] with different F3 values: the original, one with F3 either lowered or raised by 30% in frequency, and one with F3 removed. The vowel [a:] was extracted from the simulated emotions, inverse filtered and manipulated. The resulting 12 synthesized samples were randomized and presented to 30 listeners who evaluated the valence (positiveness/negativeness) of the expressions. The vowel with raised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…This material was also used in earlier studies. 16,33,34 From the total number of 450 samples, 200 samples were randomly chosen for the analyses of the present study. It was considered that 200 samples would be the maximum in the perception test that the listeners could reasonably classify without becoming too tired.…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…This material was also used in earlier studies. 16,33,34 From the total number of 450 samples, 200 samples were randomly chosen for the analyses of the present study. It was considered that 200 samples would be the maximum in the perception test that the listeners could reasonably classify without becoming too tired.…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…31 Some studies have aimed to shed light on the individual role of the acoustic voice quality 7 in the expressions of emotions and their valence. 6,16,[32][33][34] The results of Laukkanen et al suggested that voice source parameters may vary independently of F0 and intensity in emotional utterances. 4 In a further study by Laukkanen et al 6 the variation in F0, intensity and duration were artificially eliminated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier investigations, formant frequencies (F2-F4) have been found to be higher in positive valence than in negative valence [16,23] ]. The perceptual value of a formant, its loudness, is influenced by the amplitude of the formant and the sensitivity of hearing at the frequency range of the formant.…”
Section: Discussionmentioning
confidence: 99%
“…An intraword vowel [a:] has commonly been used in voice analyses that apply glottal inverse filtering [e.g., [18,19,20]], as well as in some EGG studies [e.g., [21,22,23]]. A reading task to furnish connected speech material has been recommended for research purposes, while spontaneous speech has been recommended for clinical use [24].…”
Section: Introductionmentioning
confidence: 99%